Management of Extracurricular Activities In Improving Student Achievement At Madrasah Tsanawiyah Bustanul Faizin - Gibol, Abdurrahman; Santoso, Muhammad Deni (Manunggal Halim Jaya, 2024)
This study aims to describe and analyze the management of extracurricular activities at Madrasah Tsanawiyah Bustanul Faizin and its contribution to improving students' non-academic achievements. Extracurricular management is an organized process that includes planning, organizing, implementing, and supervising activities outside of class hours aimed at developing students' potential, interests, and talents. Based on an Islamic management approach, these activities are also directed at shaping students' spiritual character and responsibility. This research uses a qualitative approach with data collection techniques through interviews. The results showed that extracurricular management in the madrasah has been running well. Planning is carried out regularly at the beginning of the school year through coordination meetings. Organizing includes the distribution of tasks to coaches according to their fields of expertise. Implementation focuses on fostering students through various positive activities, while supervision is carried out by comparing actual conditions with predetermined standards and followed by corrective action if necessary. The implementation of effective extracurricular management significantly contributes to the improvement of students' non-academic achievements. This is evidenced by the various awards won by students in district and provincial level competitions. Thus, extracurricular management that is structured and based on Islamic values has proven to be a means of character building and improving the overall quality of students.